Research on Obstacle Avoidance and Environment Adaptability of Snake Robot Based on Deep Learning - Qi, Wei; Ying, Chun; Yong, Sheng; Zhao, Guizhi; Wang, Lihua (Bright Publisher, 2022)
With the development and popularization of computer artificial intelligence technology, more and more intelligent machines are gradually produced. These intelligent machines have brought great convenience to people's lives.This paper studies the control method of snake robots based on environment adaptability, which mainly explains the construction and stability of multi-modal CPG model. In addition, this paper also studies the trajectory tracking and dynamic obstacle avoidance of mobile robot based on deep learning.